2017
DOI: 10.1016/j.eats.2017.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Assisted Posteromedial Portal Placement of the Elbow Joint to Prevent Ulnar Nerve Injury

Abstract: Direct posterior and posterolateral portals are the standard portals used in posterior elbow arthroscopy. A posteromedial portal in the elbow is not recommended because of its proximity to the ulnar nerve. However, iatrogenic injuries to the ulnar nerve have been reported after elbow arthroscopy using the standard posterior portals, especially in posteromedial elbow joint pathologies. We present a surgical technique applicable to posteromedial elbow pathology by using ultrasound-assisted posteromedial portal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Ohuchi et al [ 16 ] presented a technique applicable to portal placement of the elbow using an ultrasound-assisted method. However, they did not perform this technique in a large number of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ohuchi et al [ 16 ] presented a technique applicable to portal placement of the elbow using an ultrasound-assisted method. However, they did not perform this technique in a large number of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Powell et al [ 15 ] reported that map planning surgical access would benefit from preoperative sonography of the ulnar nerve. In addition, Ohuchi et al [ 16 ] concluded that ultrasound-assisted posteromedial portal placement of the elbow joint avoids ulnar nerve injuries; however, reports on the use of assistive techniques to establish an anterolateral approach are limited.…”
Section: Introductionmentioning
confidence: 99%
“…The latter may lead to accidental entanglement or suction injury of the ulnar nerve, as the medial capsule forms only a thin barrier between the arthroscopic working space and the nerve. The posteromedial portal is generally not used, as it directly overlies the ulnar nerve [21, 28].…”
Section: Discussionmentioning
confidence: 99%
“…US-guided repair techniques have been reported as the "third generation" procedures for acute Achilles tendon rupture [19], medial collateral ligament [20] and medial patellofemoral ligament tear of the knee [21], and anterior talofibular ligament injury in the ankle [22][23][24]. Some arthroscopic surgeons found it helpful to guide arthroscopic procedures with ultrasound [25][26][27][28].…”
Section: Us-guided Surgery In Msk Medicinementioning
confidence: 99%